The Feasibility of Implementing Pay-As-You-Drive in Singapore. - Han, Yu. (2008)
According to our research, Singapore consumers are interested in buying PAYD if it is introduced in Singapore. The main factors affecting their decisions are “resistance to changes and unfamiliarity with PAYD”, “save and control premium”, “perception of fairness” and “inconvenience”. Results show that people who drive less, have higher income and have education level of “university” are more likely to use PAYD.